2016
DOI: 10.1007/s12576-016-0514-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to microgravity, deconditioning, and countermeasures

Abstract: Humans are generally in standing or sitting positions on Earth during the day. The musculoskeletal system supports these positions and also allows motion. Gravity acting in the longitudinal direction of the body generates a hydrostatic pressure difference and induces footward fluid shift. The vestibular system senses the gravity of the body and reflexively controls the organs. During spaceflight or exposure to microgravity, the load on the musculoskeletal system and hydrostatic pressure difference is diminishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 114 publications
1
85
0
4
Order By: Relevance
“…Our results have implications to the cardiovascular deconditioning that occurs during space missions. Similarly to HDT, microgravity causes a headward shift of body fluid that in the short term elicits a reduction of blood pressure and heart rate, and in the long term leads to a reduction of baroreflex sensitivity and ultimately to orthostatic intolerance [30,20,16,53]. In this study, we showed that loading the antigravity muscles during HDT at rest causes an increase of BP that can establish similar values to those associated to orthostatic condition (i.e.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Our results have implications to the cardiovascular deconditioning that occurs during space missions. Similarly to HDT, microgravity causes a headward shift of body fluid that in the short term elicits a reduction of blood pressure and heart rate, and in the long term leads to a reduction of baroreflex sensitivity and ultimately to orthostatic intolerance [30,20,16,53]. In this study, we showed that loading the antigravity muscles during HDT at rest causes an increase of BP that can establish similar values to those associated to orthostatic condition (i.e.…”
Section: Discussionmentioning
confidence: 49%
“…To better interpret these cardiovascular responses, it is therefore important to determine the potential role of antigravity muscle activity on cardiovascular function. Establishing this role may also contribute to a better understanding of the cardiovascular deconditioning caused by microgravity [20,16,53,7,57,8], and of the physiological processes involved in recovery from physical exercises during space missions [15,54].…”
Section: Introductionmentioning
confidence: 99%
“…Microgravity in space causes various problems in different biological systems, including muscular system atrophy, immune system dysfunction, electrolyte imbalance and cardiovascular anomalies (Grimm et al, 2016;Tanaka, Nishimura, & Kawai, 2017). One of the most prominent and well recognized physiological challenges accompanying extended spaceflight is bone mass reduction and osteopenia (Grimm et al, 2016;Sun et al, 2018).…”
Section: The Primary Cilium As a Coordinator In Signal Transductionmentioning
confidence: 99%
“…Numerous attempts have been taken to replace missing gravitational loads by exercise‐based countermeasures, for example, resistance exercise . Currently, astronauts on the International Space Station (ISS) use three different exercise‐based countermeasures: treadmill, cycle ergometer, and the “Advanced Resistive Exercise Device (ARED).” Astronauts are recommended to exercise for at least two hours per day but muscle atrophy can only be reduced and not avoided with the current training regiments . This may be due to training mode or training protocols but also motivational aspects have to be taken into account as daily exercise session of two hours are not kept up by all individuals living on the ISS.…”
Section: Introductionmentioning
confidence: 99%
“…Astronauts are recommended to exercise for at least two hours per day 9 but muscle atrophy can only be reduced and not avoided with the current training regiments. 10 This may be due to training mode or training protocols but also motivational aspects have to be taken into account as daily exercise session of two hours are not kept up by all individuals living on the ISS. Therefore, different training methods and protocols are continuously investigated in order to optimize exercise-based countermeasures with regards to crew time and effectiveness.…”
mentioning
confidence: 99%